Zustand und Entwicklung wirtschaftlich wichtiger Grundfischbestände im Nordost-Atlantik - Schöne, Rüdiger (1995)
A review of the NE Atlantic stocks of cod, haddock, saithe, redfish and Greenland halibut is given. The results are based on the assessments of the ICES "Arctic Fisheries Working Group" and the critical examination of the ICES "Advisory Committee on Fisheries Managment (ACFM)".